Hierarchical collaborative expansion planning for transmission and distribution networks considering transmission cost allocation. (1st February 2022) - Zhong, Haiwang; Zhang, Guanglun; Tan, Zhenfei; Ruan, Guangchun; Wang, Xuan
Abstract: Expansion planning for transmission networks and distribution networks has been widely investigated. For those entities that manage transmission and distribution assets, it is essential to develop a collaborative plan for both networks under coupling constraints, such as a total budget limitation constraint. Here, two technical issues should be considered: the high complexity of the integrated planning model due to the coupling of transmission and distribution networks and the inefficient allocation of the transmission cost (which is a major part of the total fixed cost of power systems). Based on an equivalent model of distribution network expansion planning proposed in our previous work, this paper designs a hierarchical collaborative expansion planning framework for transmission and distribution networks that efficiently allocates the transmission cost. Formulations of a conventional integrated model and the proposed hierarchical model are compared to show how the equivalent model of the distribution network can reduce the model's complexity. Case studies conducted on both a small-scale case (Garver's 6-bus system) and a large-scale case (IEEE 118-Bus system) demonstrate the effectiveness of the proposed framework by approximately decomposing the complex integrated planning model into several small-scale tractable models with high accuracy. Case studies also indicate that considering the transmission cost allocation in the electricity prices during collaborative expansion planning will decrease the total planning and operating costs. Highlights: A hierarchical planning model for transmission–distribution networks is proposed. Transmission cost allocation and network coupling constraints are incorporated. An iterative algorithm, together with a termination criterion is designed. The effectiveness of proposed method is verified on case systems of multi-scales.